Potential Sedative and Therapeutic Value of Dexmedetomidine in Critical COVID-19 Patients - Saeid Safari; Alireza Jahangirifard; Alireza Zali; Alireza Salimi; Ehsan Bastanhagh; Reza Aminnejad; Reza Jalili Khoshnood; Davood Ommi (Tabriz University of Medical Sciences, 2021)
The coronavirus 2019 disease (COVID-19) is an ongoing outbreak of respiratory disease, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The virus can invade various tissues and organs, causing multiple organ dysfunctions. Critically ill COVID-19 patients may develop acute respiratory distress syndrome and pneumonia, which are the major causes of hypoxemic respiratory failure and death due to SARS-CoV-2 infection. Thus, ventilation support(invasive or noninvasive), has become a common practice in respiratory treatment of COVID-19patients. Patients receiving mechanical ventilation usually require sedation to alleviate anxiety, pain and discomfort. On the other hand, current clinical reports have indicated that a significant number of COVID-19 patients require prolonged intensive care unit (ICU) care and ventilation, which increases the risk of delirium. Thus, selection of appropriate sedative medications during this period is of utmost importance. Dexmedetomidine (DEX) is a sedative, anxiolytic and analgesic agent that acts through the α2-adrenoceptor. Its sedative property is notable due to the lack of respiratory depression. In addition, its cytoprotective, immunoregulatory and anti-inflammatory properties have been well established in preclinical settings. Based on these features, a number of recent studies have proposed DEX as a beneficial sedative agent that simultaneously mitigates the excessive inflammation and protects vital body organs in patients with severe COVID-19. Incurrent brief review, we aimed to discuss the therapeutic benefits of DEX in managing different indications of COVID-19.